ANALYSIS OF THE INTERN ELIGIBILITY RECOMMENDATION SYSTEM FOR INTERNSHIP USING THE SPECIFIC-MEASURABLE-ACHIEVABLE-RELEVANT-TIME BOUND METHODOLOGY AT PT PELINDO IV MAKASSAR - Suardi Hi Baharuddin; Andra Resquillah; Mulyanti Lestari (Nusantara Hasana Journal, 2023)
An Internships is an activity carried out in the world of work as learning, education, or training tailored to competencies in their fields. Manual processes involving information gathering and student eligibility assessments have traditionally experienced difficulties and delays. In addition, the criteria used to evaluate student eligibility also tend to be subjective and not objectively measurable. Simple Multi-Attribute Ratting Technique is a decision-making method that uses the elements of the decision matrix as an estimate of each alternative for all criteria, as well as takes into account the normalization of the elements of the decision matrix. Based on the data in Table 13, the results of the calculation process using the SMART method are known that alternative students A3 and A2 are the most worthy of being recommended to carry out MPAs at PT Pelindo IV Makassar with a value of >= 0.50. It is concluded that through the application of the SMART method, recommendations can be made on the eligibility of intern at PT Pelindo IV so that prospective intern can be selected objectively. Suggestions for future research are to use hybrid techniques against multiple methods that can support the recommendation process, as well as use more specific criteria.